Habitat model forecasts suggest potential redistribution of marine predators in the southern Indian Ocean. (29th November 2021) - Reisinger, Ryan R.; Corney, Stuart; Raymond, Ben; Lombard, Amanda T.; Bester, Marthán N.; Crawford, Robert J. M.; Davies, Delia; de Bruyn, P. J. Nico; Dilley, Ben J.; Kirkman, Stephen P.; Makhado, Azwianewi B.; Ryan, Peter G.; et al.
Abstract: Aim: Climate change will likely lead to a significant redistribution of biodiversity in marine ecosystems. We examine the potential redistribution of a community of marine predators by comparing current and future habitat distribution projections. We examine relative changes among species, indicative of potential future community‐level changes and consider potential consequences of these changes for conservation and management. Location: Southern Indian Ocean. Methods: We used tracking data from 14 species (10 seabirds, 3 seals and 1 cetacean, totalling 538 tracks) to model the habitat selection of predators around the Prince Edward Islands. Using random forest classifiers, we modelled habitat selection as a response to a static environmental covariate and nine dynamic environmental covariates obtained from eight IPCC‐class climate models. To project the potential distribution of the predators in 2071–2100, we used climate model outputs assuming two greenhouse gas emission scenarios: RCP 4.5 and RCP 8.5. Results: Analogous climates are projected to predominantly shift to the southeast and southwest. Species' potential range shifts varied in direction and magnitude, but overall shifted slightly to the southwest. Despite the variable shifts among species, current species co‐occurrence patterns and future projections were statistically similar. Our projections show that at least some important habitats will shift out of national waters and marine protected areas by 2100, but important habitat area will increase in the Convention on the Conservation of Antarctic Marine Living Resources Area. Predicted areas of common use among predators decreased north of the islands and increased to the south, suggesting that multiple predator species may use southerly habitats more intensively in the future. Consequently, Southern Ocean management authorities could implement conservation actions to partially offset these shifts. Main conclusions: Overall, we predict that marine predator biodiversity in the southern Indian Ocean will be redistributed, with ecological, conservation and management implications.